Insertion of Religious Moderation in Islamic Religious Education in Madrasah - Asrohah, Hanun; Junaedi, Junaedi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to examine the insertion of religious moderation policies in Islamic Religious Education in madrasas. This study uses qualitative research with a policy research approach. The data collected are about characteristics of religious moderation policy insertion in learning Islamic Religious Education in madrasas. Data were collected from various regulations related to religious moderation and education policies in madrasas. Data were analyzed using content analysis. The results of the study indicate that the insertion of religious moderation in Islamic Religious Education learning is rational-incremental and responsive. Rational-incremental policies mean the hierarchy and structural relations of policymakers in the interest of realizing a tolerant and harmonious religious life. Responsive policies are seen from the patterns of interaction between policymakers and policy implementers who involve the community so that they reflect a sense of justice in society and accommodate community participation.